Brevibacillus sp: a novel thermophilic source for the production of bile salt hydrolase - Sridevi, N.; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2009)
A thermophilic microorganism growing within the temperature range of 40-65 A degrees C (optimum at 55 A degrees C) was isolated from hot water springs near Konkan, Maharashtra, India. Based on 16S rDNA sequence analysis, it was concluded that the isolate belongs to the genus Brevibacillus. The present paper reports the isolation, identification, and standardization of fermentation conditions for the production of enzyme, bile salt hydrolase (EC 3.5.1.24) which is produced intracellularly at high temperatures. This is the first report regarding the production of bile salt hydrolase from a thermophilic source. Optimization of fermentation conditions resulted in a 2.9-fold enhancement in enzyme production.
Keywords: Bile salt hydrolase; Brevibacillus sp; Fermentation; Glycodeoxycholic acid; Hot springs; Thermophile